Relationship of serum levels of interleukin 6, interleukin 8, and C-reactive protein with forced expiratory volume in first second in patients with mustard lung and chronic obstructive pulmonary diseases: systematic review and meta-analysis - Shahriary, Alireza; Panahi, Yunes; Shirali, Saeed; Rahmani, Hossein (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : The chronic systemic inflammation is a result of releasing inflammatory cytokines from the cells relating to the body immunity system and chronic activation of the innate immunity system. Aim : To evaluate the relationship among serum levels of interleukin 6 (IL-6), interleukin 8 (IL-8), C-reactive protein (CRP) with forced expiratory volume in 1st s (FEV1) in patients with mustard lung (ML) and chronic obstructive pulmonary diseases (COPD). Material and methods : A published literature search was performed through SID, web of science, ISI, Science Direct, Scopus, Medline, and PubMed databases for articles published in English. The correlation coefficient (r) and 95% confidence intervals (95% CIs) were calculated using random or fixed effects models. Heterogeneity was assessed using χsup>2 and I 2 statistics. Results : In total, 4 published studies were included in the final analysis. Using the random-effect model, meta-analysis showed that the r was –0.052 (95% CI: –0.14–0.049, p = 0.28) at serum level of IL-8, serum levels of CRP and FEV1 in these results were r = –0.13, p = 0.012, serum levels of tumor necrosis factor (TNF) and FEV1 levels were r = –0.39, p = 0.03 in the conducted studies on mustard lung patients. The IL-6 serum level was explored in COPD patients. The results of the given studies in these patients are r = –0.006, 95% CI: –0.37–0.15, and p = 0.44. Conclusions : In this meta-analysis, there was evidence that serum levels of CRP and TNF have been significantly increased in chronic obstructive pulmonary diseases compared to the healthy control group, which signifies the presence of systemic inflammation in ML and COPD patients.